Composite materials containing chromophores with 3, 7-(di)vinylquinoxalinone π-electron bridge doped into PMMA: Atomistic modeling and measurements of quadratic nonlinear optical activity. (November 2018) - Fominykh, Olga D.; Kalinin, Alexey A.; Sharipova, Sirina M.; Sharipova, Anastasiya V.; Burganov, Timur I.; Smirnov, Maxim A.; Vakhonina, Tatyana A.; Levitskaya, Alina I.; Kadyrova, Alfira A.; Ivanova, Nataliya V.; Khamatgalimov, Ayrat R.; Nizameev, Irek R.; et al.
Abstract: Two novel chromophores with dibutylaniline donor moiety, 3, 7-(di)vinylquinoxalinone π-electron bridge and tricyanofuranyl or dicyanovinyl acceptor moieties are synthesized and their properties were systematically investigated. Atomistic modeling of PMMA-based composites with the developed chromophores as guests is performed and nonlinear optical activity is studied for the first time. Atomistic modeling performed in the amorphous cell has shown that chromophore content 20 wt% may be considered most favorable for achievement of optimal d33 values for 7-DBA-VQ on V-TCF/PMMA material. Various non-covalent interactions both between chromophores and polymer matrix and chromophores inter se were revealed in the course of modeling; these interactions could contribute to the relaxation stability of orientational order and thus quadratic NLO response. Composite material 7-DBA-VQ on V-TCF/PMMA is characterized by nonlinear-optical coefficient, d33, values of 97, 111 and 47 pm/V at chromophore content of 10, 20 and 30 wt%, respectively. Thus chromophore content 20 wt% provides maximal value of NLO coefficient, what is in agreement with the obtained theoretical data. The d33 value for 7-DBA-VQ on V-DCV/PMMA is 2.5 times smaller than that for 7-DBA-VQ on V-TCF/PMMA at the same chromophore load (20 wt%). Graphical abstract: Image 1 Highlights: Atomistic modeling of composite polymer materials with NLO chromophores guests. Synthesis and structure-property relationships of new quinoxalinone-based chromophores. High values of NLO coefficients.